Effect of Al content on the oxidation behavior of Y/Hf-doped AlCoCrFeNi high-entropy alloy. (1st July 2020) - Lu, Jie; Chen, Ying; Zhang, Han; Li, Ling; Fu, Liming; Zhao, Xiaofeng; Guo, Fangwei; Xiao, Ping
Graphical abstract: Highlights: Three types of Y/Hf-doped AlCoCrFeNi high-entropy alloys with different Al content were fabricated and investigated. The fast establishment of exclusive α-Al2 O3 scale in the early oxidation stage is related to the featured nanostructure in the alloy. Both the fast establishment of exclusive α-Al2 O3 scale and the strong REs-effects contribute to the extremely slow oxidation rate. The oxidation rate gradually reduces with the increasing Al content, which results from the increasing columnar grain size of oxide scale. Abstract: In this study, three types of Y/Hf-doped AlCoCrFeNi high-entropy alloys (HEAs) with different Al content were manufactured and their oxidation behavior at 1100 °C was systematically studied. Depending on the Al content, the HEAs show two-phase or triple-phase microstructure. All HEAs exhibit extremely slow oxidation rate and meanwhile the oxidation rate gradually reduces with the increasing Al content resulting from the gradually increasing columnar grain size in the α-Al2 O3 scale. The extremely low oxidation rate and the strong interfacial bonding make the innovative Y/Hf-doped HEAs to be promising materials for high temperature oxidation resistance.